Influence of vineyard posts type on the chemical and sensorial composition of Sauvignon blanc and Merlot noir wines - Panzeri, Valeria (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScAgric)--Stellenbosch University, 2013.